Analysis of The Determinants of The Velocity of Money in ASEAN Countries for The Period 2013-2023 - Amalia, Shafira Rosa; Girindra Mega Paksi (Contemporary Studies in Economic, Finance and Banking, 2025)
This study aims to analyze the factors that influence the velocity of money circulation in ASEAN countries. The variables used are macroeconomic variables including economic growth, interest rates, inflation, and money supply. This study is quantitative and explanatory research using purposive sampling in ASEAN countries for the period 2013-2023. The analysis was carried out using panel data regression and classical assumption tests, including autocorrelation, multicollinearity, and heteroscedasticity tests. The results of the study show that economic growth and interest rates have a positive and significant effect on the velocity of money circulation. Meanwhile, inflation does not affect the velocity of money circulation, and the velocity of money circulation in Indonesia has a higher average than other ASEAN countries. This study recommends expanding the scope of data, regions, and research periods and considering other structural variables.